Cooperative modalities in robotic tele-rehabilitation using nonlinear bilateral impedance control. (October 2017) - Sharifi, Mojtaba; Behzadipour, Saeed; Salarieh, Hassan; Tavakoli, Mahdi
Abstract: A nonlinear model reference adaptive bilateral impedance controller is proposed that can accommodate various cooperative tele-rehabilitation modes for patient–therapist interaction using a multi-DOF tele-robotic system. In this controller, two reference impedance models are implemented for the master and slave robots using new model reference adaptive control laws for the nonlinear bilateral teleoperation system. "Hand-over-hand" and "adjustable-flexibility" are two modes of patient–therapist cooperation that are realized using the proposed strategy. The Lyapunov-based stability proof guarantees the patient's and the therapist's safety during the cooperation and interaction with robots, even in the presence of modeling uncertainties of the multi-DOF teleoperation system. The performance of the proposed bilateral impedance controller is experimentally investigated for upper-limb tele-rehabilitation in the two mentioned cooperation modes. Highlights: A nonlinear model reference adaptive bilateral impedance controller is proposed. Cooperative tele-rehabilitation is realized using a multi-DOF tele-robotic system. "Hand-over-hand" and "adjustable-flexibility" are two modes of patient-therapist cooperation. A Lyapunov-based stability proof guarantees the patients and the therapist's safety.